Puisi Gus Mus “Talbiyah Dalam Kesendirian’’ Sebagai Alternatif Dakwah Pada Masa Pandemi Covid-19 - Lina Masruuroh; Hafifah Aprianti; Mohammad Fajar Amertha (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
Poetry is an expression of the soul that abstracts, summarizes the atmosphere of ideas in transcendental life and human experience, which is why da'wah messages can still be conveyed through poetry. One such poem was created by Gus Mus, with the titled Talbiyah dalam Kesendirian. The poem succeeded in touching feelings and attracting the attention of many audiences on Instagram social media, because it is considered very relevant to the pandemic situation and the conditions experienced by many people in the world during the pandemic mass. This study aims to explore the semantics of Talbiyah dalam Kesendirian poetry. The theory used is semantics. The study methodology used is qualitative with a library study approach. The analysis was carried out by identifying the elements of meaning including lexical - grammatical, referential - non-referential, denotative - connotative, words - terms, conceptual - associative, idiomatic - proverbs, and figurative meanings. The results of the study show (1) the meaning of the poem contains a message of da'wah in the form of reflections on glorifying the Oneness of Allah SWT, God's response to humans who have only been encouraging to this group of people, reflection on a request to God to lead back on the path that right at His command. (2) This solitude poetry can be used as an alternative to da'wah during the pandemic.